2006
DOI: 10.1177/1352458506070605
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-β modulates bone-associated cytokines and osteoclast precursor activity in multiple sclerosis patients

Abstract: IFN-beta treatment induces complex, specific and time-dependent changes in multiple proteins and mRNAs related to bone homeostasis in MS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…BMD values from persons with MS were adjusted for BMI in less than half of the published studies [24,26,30,33,39]. Not unexpectedly, BMD at the femoral neck and lumbar spine are associated with current ambulatory function and possibly physical activity during growth, indicating a major effect of exercise and mechanical loading at these skeletal sites.…”
Section: Discussionmentioning
confidence: 99%
“…BMD values from persons with MS were adjusted for BMI in less than half of the published studies [24,26,30,33,39]. Not unexpectedly, BMD at the femoral neck and lumbar spine are associated with current ambulatory function and possibly physical activity during growth, indicating a major effect of exercise and mechanical loading at these skeletal sites.…”
Section: Discussionmentioning
confidence: 99%
“…Combinatory medication of IFNa and Ribavirin (in the case of Hepatitis C) is under debate as it affects bone mineral density (Solis-Herruzo et al, 2000;Hofmann et al, 2008). There are also indications that medications including IFNb affect the RANK/RANKL system and may modulate bone phenotypes in MS patients (Weinstock-Guttman et al, 2006). Therefore, an understanding of type I IFN-mediated effects on bone is of great interest to improve medication and circumvent potential bone side effects.…”
mentioning
confidence: 98%
“…Nevertheless, they received continuous IFN-β treatment that may also affect the RANKL/OPG system. In a small cohort of RR-MS patients, it was shown that IFN-β caused an immediate upregulation of serum sRANKL and OPG levels, with a long-term increase in the bone formation marker, osteocalcin [36]. The study by Zhao et al [37] showed that IFN-β administration increased the serum level of OPG and did not affect serum RANKL a week after treatment in rheumatoid arthritis patients.…”
Section: Discussionmentioning
confidence: 96%
“…Weinstock-Guttman et al [36] assessed the dynamic of RANKL and OPG expression in the PBL of RR-MS patients during IFN-β treatment, showing higher induction within 48 h compared to in the control group. Another group of authors compared serum levels of sRANKL and OPG as well as a number of bone markers, in RR-MS patients and controls, showing higher sRANKL and OPG levels in RR-MS [21].…”
Section: Discussionmentioning
confidence: 99%